Water security and the pursuit of food, energy, and earth systems resilience. Issue 8 (17th November 2018) - Scott, Christopher A.; Albrecht, Tamee R.; De Grenade, Rafael; Zuniga-Teran, Adriana; Varady, Robert G.; Thapa, Bhuwan
ABSTRACT: This article addresses the emergence and interrelation of food, energy, and water security in terms of resource use and the ensuing societal and environmental outcomes. For decades, food security and energy security have been well-accepted, operational concepts. Water security is the latest entrant, yet the implications of water insecurity for food, energy and earth systems resilience have not been adequately considered. This article examines how and why this is so – particularly with growing water scarcity and insecurity that may compete with energy and food security – and emphasizes the critical need to link water-energy-food nexus approaches to earth systems resilience.